2008
DOI: 10.1038/nrn2374
|View full text |Cite
|
Sign up to set email alerts
|

The neural systems that mediate human perceptual decision making

Abstract: Perceptual decision making is the act of choosing one option or course of action from a set of alternatives on the basis of available sensory evidence. Thus, when we make such decisions, sensory information must be interpreted and translated into behaviour. Neurophysiological work in monkeys performing sensory discriminations, combined with computational modelling, has paved the way for neuroimaging studies that are aimed at understanding decision-related processes in the human brain. Here we review findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
642
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 808 publications
(736 citation statements)
references
References 103 publications
57
642
2
17
Order By: Relevance
“…In the current study, the dlPFC encoded individual cue weights as well as combined SoE, indicating that this region may be directly involved in the cue integration process. This is consistent with prior reports demonstrating engagement of the dlPFC in evidence accumulation during perceptual decision-making (Gold and Shadlen, 2007;Heekeren et al, 2008), and encoding of ambiguity or difficulty in multi-attribute decision-making (Kahnt et al, 2011;Krebs et al, 2012). Our results further demonstrate involvement of the fronto-parietal control network in a feature-invariant evidence integration processes, possibly guiding attention to cues according to their weighted importance and tracking uncertainty in choices.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the dlPFC encoded individual cue weights as well as combined SoE, indicating that this region may be directly involved in the cue integration process. This is consistent with prior reports demonstrating engagement of the dlPFC in evidence accumulation during perceptual decision-making (Gold and Shadlen, 2007;Heekeren et al, 2008), and encoding of ambiguity or difficulty in multi-attribute decision-making (Kahnt et al, 2011;Krebs et al, 2012). Our results further demonstrate involvement of the fronto-parietal control network in a feature-invariant evidence integration processes, possibly guiding attention to cues according to their weighted importance and tracking uncertainty in choices.…”
Section: Discussionsupporting
confidence: 92%
“…Guerin andMiller 2011). This interpretation is supported by prior research suggesting that IPS activity during perceptual decisions in humans (Ploran et al 2007;Heekeren et al 2008;Tosoni et al 2008;Kayser et al 2010;Ploran et al 2011, cf. Ho et al 2009Guerin and Miller 2011) and lateral intraparietal activity in nonhuman primates Newsome 1996, 2001;Schall 2003;Kiani et al 2008;Kiani and Shadlen 2009) is associated with the accumulation of evidence to guide perceptual decision making.…”
Section: Dorsal Ppc: Lateral Ips Versus Splsupporting
confidence: 75%
“…In humans, a number of studies have identified a frontoparietal network involved in processes during perceptual decisions, including sensory processing, attentional control, evidence accumulation, and motor planning (Heekeren et al, 2008;Kayser et al, 2010a,b;Liu and Pleskac, 2011;Ploran et al, 2007Ploran et al, , 2011Rowe et al, 2010;Ho et al, 2009;Tosoni et al, 2008). Previously we demonstrated that for subjects performing a dot motion discrimination task, this network displays a blood oxygen level-dependent (BOLD) response that varies inversely with motion coherence (Kayser et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%